Effect of NK4 Transduction in Bone Marrow-Derived Mesenchymal Stem Cells on Biological Characteristics of Pancreatic Cancer Cells - Yun-Peng Sun (International Journal of Molecular Sciences, 2014)
Pancreatic cancer usually has a poor prognosis, and no gene therapy has yet been developed that is effective to treat it. Since a unique characteristic of bone marrow-derived mesenchymal stem cells (MSCs) is that they migrate to tumor tissues, we wanted to determine whether MSCs could serve as a vehicle of gene therapy for targeting pancreatic cancer. First, we successfully extracted MSCs from SD rats. Next, MSCs were efficiently transduced with NK4, an antagonist of hepatocyte growth factor (HGF) which comprising the N-terminal and the subsequent four kringle domains of HGF, by an adenoviral vector. Then, we confirmed that rat MSCs preferentially migrate to pancreatic cancer cells. Last, MSCs expressing NK4 (NK4-MSCs) strongly inhibited proliferation and migration of the pancreatic cancer cell line SW1990 after co-culture. These results indicate that MSCs can serve as a vehicle of gene therapy for targeting pancreatic cancer.